Human taeniasis infection (Taenia saginata): a complex public health problem. Case report - Shirley Natali Iza; José Alejandro Iza; Julián Felipe Porras-Villamil; Mario Javier Olivera (Case Reports)
Introduction: Taeniasis is a zoonosis that can be found worldwide. It is relatively easy to diagnose and its treatment is currently effective. This paper describes the follow-up of a case with persistent refractory taeniasis.